2022
DOI: 10.3389/fphar.2021.785770
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Safety Monitoring of Rituximab (Biosimilar Novex® and the Innovator) in Pediatric Patients With Complex Diseases

Abstract: Although rituximab is widely used off-label for complex pediatric diseases, safety reports are limited. We aimed to report evidence of its use in clinical practice, to describe the incidence of adverse drug reactions (ADR) to rituximab biosimilar Novex® and innovator, and to identify risk factors for the development of ADR in a real-life follow-up cohort of pediatric patients with complex diseases. We conducted a prospective, longitudinal, observational, single-centre study in patients that received rituximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Among the reasons for the different half-life (or estimate of K E ) obtained in the current evaluation, the presence of anti-drug antibodies (ADAs) represents a plausible explanation. Even though we were not able to measure ADAs, 42.3% of our patients developed infusion-related reactions [17], which may contribute to the development of ADAs as suggested by Oomen et al [38], who showed that ADAs-positive children had a higher frequency of infusion-related adverse drug reactions, lower frequency of B cell depletion, and undetectable rituximab levels due to a higher clearance or K E . Thus, measurement of ADAs would be required in future studies to contribute to the understanding of associations of ADA presence and quantity with rituximab efficacy and toxicity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Among the reasons for the different half-life (or estimate of K E ) obtained in the current evaluation, the presence of anti-drug antibodies (ADAs) represents a plausible explanation. Even though we were not able to measure ADAs, 42.3% of our patients developed infusion-related reactions [17], which may contribute to the development of ADAs as suggested by Oomen et al [38], who showed that ADAs-positive children had a higher frequency of infusion-related adverse drug reactions, lower frequency of B cell depletion, and undetectable rituximab levels due to a higher clearance or K E . Thus, measurement of ADAs would be required in future studies to contribute to the understanding of associations of ADA presence and quantity with rituximab efficacy and toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…Despite previous reports have been published on the safety assessment of interchangeability of biosimilar and innovator rituximab [17], information on pharmacological and clinical efficacy upon substitution is still scarce for the paediatric population [18].…”
Section: Introductionmentioning
confidence: 99%